Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I'm preparing for a test tomorrow and going over some reading material, and I came across this problem that was worked out. So far I think I'm following each step of logic, but I've hit a wall with this part:

(p $\land$ ($\lnot$(r $\land$ q))) $\lor$ (($\lnot$p $\lor$ (r $\land$ q)))

is logically equivalent to

(p $\lor$ $\lnot$p $\lor$ ((r $\lor$ q)) $\land$ (($\lnot$(r $\land$ q)) $\lor$ $\lnot$p $\lor$ (r $\lor$ q))

I'm stumped as to what law is applied that allows you to go from the first and conclude the second.

share|cite|improve this question
They’re both tautologies. – Brian M. Scott Jun 4 '13 at 2:43
up vote 2 down vote accepted

if you make $s=r\wedge q$, then the first statement is written as $(p\wedge\neg s)\vee(\neg p\vee s)=(p\wedge\neg s)\vee\neg(p\wedge\neg s)=1$. This last equality is due to the fact that $x\vee\neg x=1$ for all $x$.

If you also make $t=r\vee q$, the second statement can be written as $p\vee\neg p\vee t\wedge(\neg s\vee\neg p\vee t)=1$, this last equality is due to the fact that $p\vee\neg p=1$ and $1\vee\cdot=1$

share|cite|improve this answer
There’s an extra parenthesis in the second one; it may be that it’s supposed to be $$\Big(p\lor\neg p\lor(r\lor q)\Big)\land\Big(\neg(r\land q)\lor\neg p\lor(r\lor q)\Big)\;,$$ in which case it reduces instead to $1\land 1$. – Brian M. Scott Jun 4 '13 at 3:04
I'm getting confused by where that first $\lnot$p comes from that appears in the second of the two lines. – Harry Tuttle Jun 4 '13 at 4:52

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.